Construction of The Accountant's Role As A Sustainability Score Player Through A Participatory Action Research Approach - Wahyuni, Nining Ika; Roekhudin; Baridwan, Zaki (Accounting Department, 2023)
Purpose — This study aims to construct the role of accountants as sustainability score players, namely as providers of information, support, and guidance in embedding sustainable business practices in MSMEs. Design/methodology/approach—This study uses a participatory action research (PAR) approach to construct the role of accountants. This approach requires the active participation of participants in each stage of the PAR cycle, starting from planning, action, observation and evaluation, and reflection. Data were collected through observation, interviews, and FGD. The data is processed by thematic analysis after going through the triangulation process to check its validity. Findings—Accountants can expand their role by acting as sustainability score players through inclusion, providing literacy, and initiating MSMEs to start sustainable business practices. Through this involvement, accountants can realize that they can position themselves as agents of change who can become role models and mediators and facilitate the movement towards sustainable business for the MSMEs they assist. Practical implications—Accountants must develop a new habitus that shows they can contribute significantly to realizing sustainable development goals. One habitus is getting used to being involved with the community, especially with MSMEs. “Engage” represents the ability of accountants to actively participate in any embedded sustainability efforts. Originality/value—The gap between value and action in sustainability accounting research shows no relationship between values derived from existing theory and practical action. This research fills this gap by using an action research approach and involving educator accountants to determine what actions need to be taken to contribute to achieving sustainable development goals.